Manajemen Pembiayaan Pendidikan Dalam Meningkatkan Mutu Pembelajaran Di SMA Al-Qonaah Balendah Kabupaten Bandung - Moh Fariz Dzikrul Kholik; Farhan Arif Alfarisi; Ahmad Syaifullah; Moh. Abdullah Azzam Al-Amiin (Journal of Management and Creative Business, 2023)
This research aims to get an overview and examine Education Funding Management in Improving the Quality of Learning at SMA Al Qona'ah Baleendah Academic Year 2021/2022. The approach used in this study is a qualitative approach, while the method uses a descriptive method. The data collection technique used is through observation, interviews and documentation studies, with research subjects as school principals, treasurers, teachers and school committees. The research location was at SMA Al Qona'ah Baleendah, Baleendah District, Bandung Regency. The results of the study revealed that: (1) Planning for financing education at Al Qona'ah Baleendah High School was carried out in a meeting or gathering of all school members. (2) Techniques for organizing education funding based on prioritized standards to enhance shared learning. (3) The implementation of education financing is carried out based on the guidelines or references of the RKAS and RAPBS and a monthly coverage response report is prepared. (4) the evaluation of financing is carried out internally and externally, namely internally carried out by the Principal and School Committee, and externally by the Provincial Education Office through the Education Office Branch.